Observed drought indices show increasing divergence across Europe. Issue 1 (December 2017) - Stagge, James; Kingston, Daniel; Tallaksen, Lena; Hannah, David
Abstract Recent severe European droughts raise the vital question: are we already experiencing measurable changes in drought likelihood that agree with climate change projections? The plethora of drought definitions compounds this question, requiring instead that we ask: how have various types of drought changed, how do these changes compare with climate projections, and what are the causes of observed differences? To our knowledge, this study is the first to reveal a regional divergence in drought likelihood as measured by the two most prominent meteorological drought indices: the Standardized Precipitation Index (SPI) and the Standardized Precipitation-Evapotranspiration Index (SPEI) across Europe over the period 1958–2014. This divergence is driven primarily by an increase in temperature from 1970–2014, which in turn increased reference evapotranspiration (ET0 ) and thereby drought area measured by the SPEI. For both indices, Europe-wide analysis shows increasing drought frequencies in southern Europe and decreasing frequencies in northern Europe. Notably, increases in temperature and ET0 have enhanced droughts in southern Europe while counteracting increased precipitation in northern Europe. This is consistent with projections under climate change, indicating that climate change impacts on European drought may already be observable and highlighting the potential for discrepancies among standardized drought indices in a non-stationary climate.